Christ-enlivened student affairs : a guide to Christian thinking and practice in the field - Glanzer, Perry L. (Perry Lynn) (ACU Press, 2020)
"How does the Christian faith inform Christian student affairs practice? How should it? Instead of placing Christ outside the realm of education, Christ should serve as the motivating and animating force for all of Christian student affairs. With Christ at the center of education, the Christian story distinctly transforms the nature of the work education professionals do. With research from a national mixed-methods study, Christ-Enlivened Student Affairs avoids the common response of anecdotal evidence by providing a catalog of some of the best thinking and practices in the field. Glanzer, Cockle, Graber, and Jeong use the framework of educational philosophies to trace how Christianity animates the who, why, what, and how of student affairs, offering evidence-based resources, and new tools for engaging new practitioners in the field, and a larger theological perspective for Christian student affairs"--